2021
DOI: 10.21203/rs.3.rs-66218/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Technology-based Health Solutions for Cancer Caregivers to Better Shoulder the Impact of COVID-19: A Systematic Review Protocol

Abstract: Background: Cancer patients are particularly vulnerable to COVID-19, partially owing to their compromised immune systems and curbed or cut cancer healthcare services caused by the pandemic. As a result, cancer caregivers may have to shoulder triple crises: the COVID-19 pandemic, pronounced healthcare needs from the patient, and elevated need for care from within. While technology-based health interventions have the potential to address unique challenges cancer caregivers face amid COVID-19, limited insights ar… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“… 25 While telehealth provided flexibility in traveling to care, challenges remain as observed in our findings and other studies. 21 , 26 Many patients and families, including older adults with cancer, may experience challenges with technology use. 27 Care teams dedicated more time to educating patients and FCGs on preparing for surgery and recovery, and the education was presented separately to patients and FCGs due to visitation policies or additional telehealth sessions were needed to communicate with FCGs.…”
Section: Discussionmentioning
confidence: 99%
“… 25 While telehealth provided flexibility in traveling to care, challenges remain as observed in our findings and other studies. 21 , 26 Many patients and families, including older adults with cancer, may experience challenges with technology use. 27 Care teams dedicated more time to educating patients and FCGs on preparing for surgery and recovery, and the education was presented separately to patients and FCGs due to visitation policies or additional telehealth sessions were needed to communicate with FCGs.…”
Section: Discussionmentioning
confidence: 99%
“…This study also was found that caregivers of cancer patients did not pay attention to their self-care, postponed visiting the doctor in case of problems, and neglected their health. Previous studies noted that the mental health of the caregivers worsened and emphasized that the caregivers experienced the most depression and anxiety due to social isolation and quarantine [4,5,7,18,22].…”
Section: Discussionmentioning
confidence: 99%
“…Interview questions were prepared in line with the literature [4,5,7]. The data were collected by using the online interview technique by conducting one-on-one interviews with semi-structured interview forms.…”
Section: Data Collectionmentioning
confidence: 99%
See 2 more Smart Citations